Rhodomyrtus tomentosa Leaf Extract Cream Suppresses MMP-1 Expression and Epidermal Thickening in UVB-Irradiated Swiss Webster Mice - Defa Agripratama Ali; Zen Hafy; Veny Larasati; Nora Ramkita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Ultraviolet B (UVB) radiation induces matrix metalloproteinase-1 (MMP-1) expression and epidermal hyperplasia, contributing to photoaging. Rhodomyrtus tomentosa (karamunting) is rich in polyphenolic compounds with documented antioxidant properties, but its in vivo photoprotective effects remain unexplored. Methods: We investigated the effects of R. tomentosa leaf extract cream at varying concentrations (0%, 12.5%, 25%, 50%) on UVB-irradiated Swiss Webster mice (n=4 per group). UVB exposure was standardized at approximately 150 mJ/cm² per session over seven consecutive days. Vitamin E cream served as a positive control. Immunohistochemical staining quantified MMP-1 expression as a percentage of positive cells, while hematoxylin-eosin histology measured epidermal thickness. Results: Kruskal-Wallis testing revealed significant differences in both MMP-1 expression (H=10.43, p=0.015) and epidermal thickness (H=10.88, p=0.012). The 25% extract concentration optimally suppressed MMP-1 expression (mean 45.94% of positive cells) compared to the untreated UVB control (89.53%). A biphasic dose-response pattern emerged, with hormetic effects observed at 50% concentration (76.45%), suggesting polyphenol pro-oxidant activity at excessive concentrations. Epidermal thickness normalized with 25% treatment (71.8 μm) versus UVB control (93.4 μm). Immunohistochemical intensity decreased progressively with treatment intensification through 25%, supporting suppression of MMP-1-mediated collagen degradation. Conclusion: R. tomentosa leaf extract cream at 25% concentration effectively suppresses MMP-1 expression and normalizes UVB-induced epidermal thickening in mice. The hormetic response at higher concentrations highlights the importance of dose optimization in phytotherapeutic development. This work establishes the first in vivo evidence for karamunting leaf extract as a photoprotective agent and supports further clinical translation.